Significant Micronutrient Imbalance Associated with Entamoeba histolytica and Giardia lamblia Infections in Children - Layla S. Abu-Hadal; Noor M. Al-Humaidy; Dumooa F. Al-Hameedawi (Academia Open, 2026)
General Background: Intestinal protozoal infections constitute a substantial public health burden in developing countries, contributing to considerable gastrointestinal morbidity among pediatric populations. Specific Background: Entamoeba histolytica and Giardia lamblia infections have been associated with malabsorption and subsequent micronutrient deficiencies in children. Knowledge Gap: Despite documented individual nutrient deficiencies, the concurrent effects of these protozoal infections on vitamin D, calcium, and vitamin C status remain inadequately characterized in Middle Eastern pediatric populations. Aims: This case-control study evaluated serum concentrations of vitamin D, calcium, and vitamin C among male children aged 1-10 years infected with E. histolytica, G. lamblia, and healthy controls in Thi-Qar Governorate, Iraq. Results: Infected children demonstrated significantly reduced micronutrient levels compared to controls (P < 0.001), with G. lamblia infection exhibiting the most pronounced deficiencies. Large effect sizes were observed for vitamin D (η² = 0.41), calcium (η² = 0.36), and vitamin C (η² = 0.52). Novelty: This investigation represents the first comprehensive assessment of multi-micronutrient deficiency patterns associated with these protozoal infections in Iraqi children. Implications: These findings underscore the necessity for integrated parasitological-nutritional interventions in clinical management protocols to optimize therapeutic outcomes and prevent long-term developmental consequences.Highlight : Children infected with Giardia lamblia showed the lowest serum vitamin D and calcium levels, indicating more severe malabsorption than Entamoeba histolytica infection. Intestinal protozoal infections were associated with concurrent deficiencies of vitamin D, calcium, and vitamin C, reflecting a multi-micronutrient depletion pattern rather than isolated deficits. Large effect sizes confirmed a strong association between protozoal diarrhea, reduced body mass index, and disturbed micronutrient homeostasis in affected children. Keywords : Intestinal protozoa, Giardia lamblia, Entamoeba histolytica, micronutrient deficiency, pediatric malnutrition